Systematic ideas in the domestic psychiatry (Bekhterev’s clinical approaches) - K. V. Bezchasniy (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
This article shown the system ideas of scientist in aspects by clinical approach, as the basic of created holistic scientific school. V.M. Bekhterev as an outstanding scientist contributed to the becoming the systematic approaches, which have influence on standing domestic psychiatry.